2013
DOI: 10.1002/j.2161-1874.2013.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Supports to Substance Abuse Service Use Among Homeless Adults

Abstract: Although there is a great need for substance abuse services among the homeless, many homeless individuals do not use those services. This study examined barriers and supports related to service use. Participants recognized a need for treatment and significant barriers to accessing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…Consistent with prior research that has identified residential instability as a barrier to accessing addiction treatment (Brubaker et al 2012), the present study identified an independent and positive relationship between homelessness and self-reported need for addiction treatment. Socioeconomically vulnerable PWUD often struggle to maintain social integration (De Vet et al 2013) and, as such, may not be effectively supported to seek treatment without the aid of targeted interventions.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with prior research that has identified residential instability as a barrier to accessing addiction treatment (Brubaker et al 2012), the present study identified an independent and positive relationship between homelessness and self-reported need for addiction treatment. Socioeconomically vulnerable PWUD often struggle to maintain social integration (De Vet et al 2013) and, as such, may not be effectively supported to seek treatment without the aid of targeted interventions.…”
Section: Discussionsupporting
confidence: 88%
“…20,22,30 Limited research has examined how the number of self-reported barriers affect vulnerable populations. However, a study by Brubaker and colleagues 6 revealed a paradoxical finding that fewer individual barriers were associated with decreased odds of accessing substance abuse services. Considering the underutilization of this measure in extant research, and its prior application to only substance abuse service among homeless adults, it remains underdeveloped as an Enabling traditional variable.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The Behavioral Model for Vulnerable Populations has frequently been applied to examine health service utilization among homeless persons 4,610 and although there is a high concordance between incarceration status and homelessness, this study seeks to offer insight on the most vulnerable timeframe when persons are transitioning back into the community. Previous literature has suggested that the model may be applicable to persons under criminal justice supervision given similar issues of vulnerability that limit access to care.…”
Section: Re-entering African American Women: a Vulnerable Populationmentioning
confidence: 99%
See 2 more Smart Citations